228k views
1 vote
Solve this system of equations usingthe substitution method.y = 4x3x – 7 = y1

Solve this system of equations usingthe substitution method.y = 4x3x – 7 = y1-example-1
User Tensigh
by
4.2k points

1 Answer

5 votes

Given:


\begin{gathered} y=4x \\ 3x-7=y \end{gathered}

Required:

To solve the given equations by using substitution method.

Step-by-step explanation:

Consider the given two equation


\begin{gathered} y=4x------(1) \\ 3x-7=y--------(2) \end{gathered}

Substitute equation (1) in (2), we get


\begin{gathered} 3x-7=4x \\ 3x-4x=7 \\ -x=7 \\ x=-7 \end{gathered}

Put x in (1), we get


\begin{gathered} y=4(-7) \\ \\ y=-28 \end{gathered}

Final Answer:


(-7,-28)

User Astreltsov
by
5.1k points